A Comparison of Forecasting Models for Carbon Dioxide Emission Quantity from Power Generation Sector - Mingkwan, Yutthachai (Journal of Science Ladkrabang, 2023)
The objective of this research is to compare forecasting models for carbon dioxide emission quantity from power generation sector using the data from Energy Policy and Planning Office, Ministry of Energy from January 2001 to December 2022 with a total of 264 months. The data was divided into 2 sets. The first set of data was collected from January 2001 to December 2021 with a total of 252 months for constructing 3 forecasting models: Box-Jenkins method, Winters’ Additive method, and Combined forecasting method. The second set of data was gathered from January to December 2022 with a total of 12 months for comparing the suitability of the forecasting models by considering the lowest root mean square error and mean absolute percentage error. The results indicated that Box-Jenkins method was the most appropriate method.